Effect Of Daily And Alternate Day Iron & Folic Acid Supplementation To Pregnant Females On The Weight Of The Newborn - Grover Vijay; Aggarwal O.P; Gupta Anita; Kumar Praveen; Tiwari R.S (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the effect of IFA supplementation when given daily and on alternate days? Objective: To study the effect of daily and alternate day IFA supplementation. Study design: Intervention study. Setting: Rural health center of Gazipur village in east Delhi under deptt, of PSM, University College of Medical Sciences, Delhi. Participants: Pregnant females with period of gestation 20Â±4 weeks registering during Jan. to Dec. 94. Sample size: 120 pregnant females. Study variables: Birth weight. Results: Total 120 pregnant females were studied. 64 were put on daily (Group I) and 56 on alternate day (group II) IFA supplementation. In group I, 7 (10.9%) babies had birth weight less than 2.5 Kg as compared to 3 (5.3%) in Group II. However, the difference between the two groups regarding the birth weight was not statistically significant (p=0.489). Supplementation of IFA in Group II caused fewer adverse effects compared to Group I. Alternate day IFA supplementation may be an alternate to daily IFA in cases of non-compliance due to adverse effects without adversely affecting the outcome of pregnancy.